2013
DOI: 10.1002/acr.21957
|View full text |Cite
|
Sign up to set email alerts
|

Choosing Where to Put Your Energy: A Qualitative Analysis of the Role of Physical Activity in the Lives of Working Adults With Arthritis

Abstract: Objective. Research points to many potential benefits of physical activity (PA) for those with arthritis. However, PA has not typically been examined within the context of other life roles. This study examined the perceptions of PA among individuals managing arthritis in addition to employment and other role demands. Methods. Eight focus groups were conducted with 24 women and 16 men (age range 29 -72 years) who were currently or recently employed (within 2 years) and had osteoarthritis or inflammatory arthrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 42 publications
3
31
0
Order By: Relevance
“…These synthesis findings emphasized that having a chronic condition further complicates the matter, since the worker needs to balance their work and personal lives while continuously managing their chronic condition and symptoms. This finding is in accordance with other literature on work-life balance and chronic conditions (Bedell, 2008;Gignac et al, 2014;Kaptein et al, 2013). Grawitch et al, who studied work-life balance in light of selfregulation, control and decision making, showed that active decisions need to be made to allocate resources, such as energy which is usually a scarce resource in workers with a chronic condition (Grawitch, Barber, & Justice, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…These synthesis findings emphasized that having a chronic condition further complicates the matter, since the worker needs to balance their work and personal lives while continuously managing their chronic condition and symptoms. This finding is in accordance with other literature on work-life balance and chronic conditions (Bedell, 2008;Gignac et al, 2014;Kaptein et al, 2013). Grawitch et al, who studied work-life balance in light of selfregulation, control and decision making, showed that active decisions need to be made to allocate resources, such as energy which is usually a scarce resource in workers with a chronic condition (Grawitch, Barber, & Justice, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Participants in the current study described numerous examples of behaviours aimed at matching their capacities to the work environment, including the prioritization of other activities to ensure they had sufficient energy to maintain their paid employment, and is consistent with the findings of others [31].…”
Section: Discussionsupporting
confidence: 71%
“…They stated that written materials alone would be insufficient to support exercise uptake, concurring with previous research [35,[37][38][39]. Exercising with and observing others with RA, in addition to receiving support from family members and friends, encouraged most participants to change their exercise behaviour, as posited by the SCT.…”
Section: Discussionsupporting
confidence: 59%